Preconcentration and Determination of Ultra Trace Cobalt(II) in Water Samples Using Co(II)-Imprinted Diazoaminobenzene-Vinylpyridine Copolymers - Tajodini, Nilofar; Moghimi, Ali (Asian Journal of Chemistry, 2010)
Cobalt(II) imprinted and non-imprinted copolymers were prepared by metal ion imprinted polymer (MIIP) technique. The copolymers were obtained by copolymerizing cobalt chloride (or without it), diazoaminobenzene (DAAB) and vinylpyridine (VP) using ethyleneglycoldimethacrylate (EGDMA) as cross-linker in the presence of 2,2'-azobisisobutryonitrile as initiator. The separation and preconcentration characteristics of the copolymers for Co(II) were investigated by batch and column procedures. The results demonstrated that the Co(II) imprinted copolymers had higher adsorption capacity with the value of 205 μmol g-1 of dry copolymer, about 3.5 times of and good selectivity for Co(II) compare to non-imprinted copolymers (58.6 μmol g-1 of dry copolymer). The distribution ratio (D) values of the Co(II) imprinted copolymers increased for Co(II) with respect to both distribution ratio values of Zn(II), Cu(II), Co(II) and non-imprinted copolymer. The relatively selective factor (αr) values of Co(II)/Cu(II), Co(II)/Zn(II), Co(II)/Fe(II), are 36.7, 51.8, 86.7, respectively. The tolerance limit for other electrolytes such as NaCl, KBr, KI, NaNO3, Na3PO4, Na2SO4 and Mg(NO3)2 is also remarkably improved with the values of 10-100-fold of the non-imprinted copolymer. The Co(II) imprinted copolymers can be used at least 20 times with ca. 96 % recoveries. Based on the packed columns with Co(II) imprinted copolymers, a highly selective solid-phase extraction (SPE) and preconcentration method for Co(II) from dilute aqueous solution was developed. The MIIP-SPE preconcentration procedure showed a linear calibration curve within concentration range from 0.13 to 25 μg L-1. The detection limit and quantification limit were 0.05 and 0.13 μg L-1 (3σ) for flame atomic absorption spectrometry (FAAS). The relative standard deviation of the eleven replicate determinations was 2.6 % for the determination of 1.0 μg of Co(II) in 100 mL water sample. Determination of Co(II) in certified tap water and rain water demonstrated that the column was good enough for Co(II) determination in matrixes containing components with similar chemical properties such as Cu(II), Zn(II), Co(II).